Influence of soybean residue flour in wheat batter formulation on physical properties of French fries / Aishah Mohd Marsin - Marsin, Aishah Mohd (Faculty of Plantation and Agrotechnology, 2023)
In this study, French fries were analyzed by using variant batter formulation with the addition of fiber. Fiber is one of food proximate sources which able to reduce the absorption of oil intake to food. Soybean grains is commonly used to make drinks or food products. Fiber could be obtained from soybean after it was crushed and its extraction were used to make foods and drinks. The output of soybean extraction was the soybean residue which able to become the food additives to reduce oil uptakes in fried food. After dehydrating and grinding process, a long-lasting soybean residue flour were obtained. The effect of soybean residue flour (SFR) addition into coating batter formulation in frying fries was studied on the color appearance and oil uptake of fries by varying the percentage of fibers at constant oil temperature. The amount of soybean residue flour in prepared batter formulation was varied (0% SFR, 10% SFR, 20% SFR). It was found that the highest fiber content (20% SRF) in batter formulation shows the lowest fat content (9g/100g) in fried fries. There is no significant difference (P>0.05) between the addition of SRF and solely using wheat batter formulation in the color appearance of French fries. All French fries’ samples using formulated SRF batter have shown similarities to French fries available in the market. Hence, the addition of soybean residue flour in wheat batter formulation influence the properties of French fries in fat content and not on the color appearance.